HUBUNGAN KARAKTER PERMUKIMAN DENGAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA (STUDI KASUS : SURODADI, KELURAHAN SISWODIPURAN DAN PERUM BUMI SINGKIL PERMAI I DESA KARANGGENENG, KECAMATAN BOYOLALI) - Inarotu Duja; Kuswanto Nurhadi; Isti Andini (Universitas Sebelas Maret Surakarta, 2015)
Every citizen who lived in settlements will definitely produce garbage, therefore the volume of waste continues to increase every time. While the final disposal is provided having a limited capacity, so that we waste management at the community level needs to be improved so that the amount of waste that goes to landfill can be reduced. Waste management at the community level is also done in Surodadi, Siswodipuran and Perum Bumi Singkil Permai (BSP) I, Karanggeneng, Boyolali. But to these two regions have different treatment in processing waste. The problem in this research is about how are the relations between the residential character and the community participation in waste management. The methos used is the methos of description that describes the relationship between the two factors through the depiction of the results of observations, questionnaires and interviews. The results of this study are the difference in terms of residential character, wate management system and participation from the community in garbage penelolaan in both regions. Economic conditions have relation with the community participation in the management of household waste. Livelihood, social, and cultural interactions taht evolve shown to has a relation with the community participation in the management of household waste. The level of income and education levels have no connection with participation from the community in waste management. Keyword : Community Participation, Residentials, Waste Management